ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK (Studi WPOP Yang Memiliki Usaha Di Kota Kudus) - Rommy Susherdianto; Haryanto Haryanto (Diponegoro Journal of Accounting, 2015)
This study aims to analyze factors that influence tax compliance personal taxpayers who have business in Kudus town. The variables which are used in this research is taxpayer’s compliance as dependent variable, taxpayer’s awareness, knowledge and understanding of tax regulations, perception of the tax system’s effectiveness, quality of service tax authorities, and tax penalties as the independent variables. This study uses quantitative research methods, where the data obtained from questionnaires with  Convenience Sampling method. Data analysis in this research uses multiple linear regression analysis with SPSS 16.00 for Windows.The results of this research are as follows: (1) taxpayer’s awareness on taxpayer’s compliance is positive and significant, (2) knowledge and understanding of tax regulations on taxpayer’s compliance is positive and significant, (3) perception of the tax system’s effectiveness did not significantly gives positive influence to taxpayer’s compliance, (4) quality of service tax authorities  on taxpayer’s compliance is positive and significant, (5) tax penalties on taxpayer’s compliance is positive and significant.